COMPRESSIVE AND SHEAR BOND STRENGTH OF OIL WELL CEMENT WITH CALCIUM CARBONATE AND SILICA FUME - Prasetyo, Arnoldus Meidio Adi; Lisantono, Ade (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2016)
One of the critical factors of cementing process in oil drilling of off-shore-project is designing the cement slurry. For this reason, the slurry properties which have been classified by American Petroleum Institute (API) should be changed so it will match with the requirement of reservoir condition. Changing the slurry properties can be done by adding the additive material into the cement slurry such as Calcium Carbonate and Silica Fume. The research objective is to study the effect of calcium carbonate and silica fume to the compressive and shear bond strength of oil well cement. Fourty five cylinder specimens with the size of (75 x 150) mm were made for compressive strength testing and fourty five cylinder specimens with the size of (25.4 x 50.8) mm were made for shear bond strength testing. Five variants of the specimen were made in this study. The variant were cement slurry with (0% Calcium Carbonate + 0 % Silica Fume) as a reference specimen; (5% Calcium Carbonate + 5 % Silica Fume); (10% Calcium Carbonate + 10 % Silica Fume); (15% Calcium Carbonate + 15 % Silica Fume); (20% Calcium Carbonate + 20 % Silica Fume). The oil well cement specimens were tested in 7, 14, and 28 days. The experimental results show that the compressive strength of oil well cement will decrease when it is added with calcium carbonate and silica fume. The shear bond strength of the oil well cement increases for the specimen with 5 % Calcium Carbonate + 5 % Silica Fume. However, the shear bond strength will decrease when content of the Calcium Carbonate + Silica Fume more than 5 %. Based on the result of this research, the optimum amount of calcium carbonate and silica fume that can be use is 5%, because with 5% of calcium carbonate and 5% of silica fume, the reducing of compressive strength is the smallest and the shear bond strength is increased compare to the others specimen with 10%, 15%, and 20% calcium carbonate and silica fume.